Meaningful thresholds for patient-reported outcomes following interventions for anterior cruciate ligament tear or traumatic meniscus injury: a systematic review for the OPTIKNEE consensus. Issue 24 (16th August 2022) - Macri, Erin M; Young, James J; Ingelsrud, Lina Holm; Khan, Karim M; Terluin, Berend; Juhl, Carsten Bogh; Whittaker, Jackie L; Culvenor, Adam G; Crossley, Kay M; Roos, Ewa M
Abstract : Objective: We synthesised and assessed credibility (ie, trustworthiness) of thresholds that define meaningful scores for patient-reported outcome measures (PROMs) following interventions for anterior cruciate ligament (ACL) tear or traumatic meniscus injury. Design: Systematic review, narrative synthesis. Data sources: We searched five databases, handsearched references of included studies and tracked citations. Eligibility: Included studies investigated: individuals with ACL tear or meniscus injury; mean age <35 years; and PROM thresholds calculated using any method to define a minimal important change (MIC) or a meaningful post-treatment score (Patient Acceptable Symptom State (PASS) or Treatment Failure). Results: We included 18 studies (15 ACL, 3 meniscus). Three different methods were used to calculate anchor-based MICs across 9 PROMs, PASS thresholds across 4 PROMs and treatment failure for 1 PROM. Credibility was rated 'high' for only one study—an MIC of 18 for the Knee injury and Osteoarthritis Outcome Score Quality-of-life (KOOS-QOL) subscale (using the MID Credibility Assessment Tool). Where multiple thresholds were calculated among 'low' credibility thresholds in ACL studies, MICs converged to within a 10-point range for KOOS-Symptoms (−1.2 to 5.4) and function in daily living (activities of daily living, ADL 0.5–8.1) subscales, and the International Knee Documentation Committee Subjective Knee Form (7.1–16.2). Other PROM thresholds differed up to 30 points. PASS thresholds converged to within a 10-point range in KOOS-ADL for ACL tears (92.3–100), and KOOS-Symptoms (73-78) and KOOS-QOL (53-57) in meniscus injuries. Conclusion: Meaningful PROM thresholds were highly susceptible to study heterogeneity. While PROM thresholds can aid interpretability in research and clinical practice, they should be cautiously interpreted.